A Case of Misdiagnosis Caused by the Coinheritance of Hb G-Siriraj [β7(A4)Glu→Lys; HBB: c.22G>A] and Hb H Disease. (2nd November 2022) - Guan, Zhi-Yang; Zhong, Ze-Yan; Xu, Zhi-Bang; Chen, Jian-Hong; Liu, Yan-Hui
Abstract: Despite the fact that most hemoglobin (Hb) variants are clinically and hematologically silent, they can interact with thalassemias, which could sometimes give rise to complicated routine thalassemia diagnostics. Hb G-Siriraj [β7(A4)Glu→Lys; HBB : c.22G>A] alone is a benign condition, but its coinheritance with α-thalassemia (α-thal) may lead to misdiagnosis. We describe the case of a Chinese woman with an elevated Hb A2 level who was assumed to carry heterozygous β-thalassemia (β-thal), but was later shown to be a double heterozygote for Hb G-Siriraj and Hb H disease. This study for the first time described hematological characteristics of a patient with a double heterozygosity for Hb G-Siriraj and Hb H disease. It is of great significance for technicians and clinicians to expand their knowledge as well as to help guide clinical diagnosis, population screening and genetic counseling.